Taʿlīm "Fatḥ al-Munjid" fī Maʿhad al-Īmān al-Islāmī lil-Banīn - yoke suryadharma (Lisanudhad: Jurnal Bahasa, Pembelajaran dan Sastra Arab, 2015)
Al-Munjid is one of the dictionaries commonly used in modern Islamic boarding schools (pesantren). It serves as an important resource for identifying the meanings of difficult vocabulary encountered by students during the learning process. Al-Munjid possesses several distinctive advantages over other dictionaries. Its extensive vocabulary places it among the most comprehensive dictionaries used in schools and universities. Moreover, its detailed explanations of word meanings facilitate learners in searching for and understanding Arabic vocabulary. This dictionary is widely used in many Islamic educational institutions, particularly those that emphasize Arabic language instruction. One example is Maʿhad al-Īmān al-Islāmī lil-Banīn, located in Ponorogo, East Java, Indonesia. At this institution, the dictionary has been incorporated into a specialized course known as "Fatḥ al-Munjid," which is taught to fifth-grade students. Through this course, students learn the techniques for effectively using Al-Munjid, culminating in a special examination on dictionary usage. For those interested in Arabic language studies, this educational practice represents a distinctive feature that sets the institution apart from many other Islamic boarding schools in Indonesia. Based on this uniqueness, the author considers that studying both this dictionary and its instructional implementation is valuable for students and teachers of Arabic. Therefore, this article provides a comprehensive explanation of the Fatḥ al-Munjid course and its implementation in the institution.